Leveraging Distinctive Competency for Competitive Advantages: Mediating of Value Creation and Moderating of Service Innovation in Indonesia's Ferry Transport Companies - Solikin, Solikin; Thamrin, HM; Majid, Suharto Abdul; Arifiani, Librita; Saribanon, Euis (SENTRALISASI, 2025)
This study aims to explain how distinctive competency can leverage the competitive advantages of Indonesia’s ferry transport companies, mediated by value creation and moderated by service innovation. A quantitative approach (positivistic paradigm) and survey methods were employed. The research population consisted of 249 directors from 42 ferry transportation companies operating on four commercial routes, with a sample size of 153. The main findings indicate that distinctive competency has a direct, positive, and significant effect on the competitive advantages of Indonesia’s ferry transport companies. Additionally, value creation mediates the relationship between distinctive competency and competitive advantages, while service innovation moderates the relationship between value creation and competitive advantages. The findings suggest that ferry transport companies in Indonesia should focus on developing and enhancing their distinctive competencies to create value and sustain competitive advantages. Moreover, investing in service innovation can strengthen the impact of value creation on competitive advantages, ensuring long-term success in a competitive market. This study contributes to the literature by integrating the roles of value creation and service innovation into the relationship between distinctive competency and competitive advantages in the context of the ferry transport industry, a sector that has received limited attention in previous research.